Active Recovery After High-Intensity Interval-Training Does Not Attenuate Training Adaptation - Wiewelhove, Thimo; Schneider, Christoph; Schmidt, Alina; Döweling, Alexander; Meyer, Tim; Kellmann, Michael; Pfeiffer, Mark; Ferrauti, Alexander (Frontiers in Physiology, 2018)
Objective: High-intensity interval training (HIIT) can be extremely demanding and can consequently produce high blood lactate levels. Previous studies have shown that lactate is a potent metabolic stimulus, which is important for adaptation. Active recovery (ACT) after intensive exercise, however, enhances blood lactate removal in comparison with passive recovery (PAS) and, consequently, may attenuate endurance performance improvements. Therefore, the aim of this study was to examine the influence of regular ACT on training adaptations during a HIIT mesocycle. Methods: Twenty-six well-trained male intermittent sport athletes (age: 23.5 ± 2.5 years; V̇O2max: 55.36 ± 3.69 ml·min·kg-1) participated in a randomized controlled trial consisting of four weeks of a running-based HIIT mesocycle with a total of 12 HIIT sessions. After each training session, participants completed 15 min of either moderate jogging (ACT) or PAS. Subjects were matched to the ACT or PAS groups according to age and performance. Before the HIIT program and one week after the last training session, the athletes performed a progressive incremental exercise test on a motor-driven treadmill to determine V̇O2max, maximum running velocity (vmax), the running velocity at which V̇O2max occurs (vV̇O2max), and anaerobic lactate threshold (AT). Furthermore, repeated-sprint ability (RSA) were determined. Results: In the whole group the HIIT mesocycle induced significant or small to moderate changes in vmax (p < 0.001, effect size [ES] = 0.65,), vV̇O2max (p < 0.001, ES = 0.62), and AT (p < 0.001, ES = 0.56) compared with the values before the intervention. V̇O2max and RSA remained unchanged throughout the study. In addition, no significant differences in the changes were noted in any of the parameters between ACT and PAS except for AT (p < 0.05, ES = 0.57). Conclusion: Regular use of individualized ACT did not attenuate training adaptations during a HIIT mesocycle compared to PAS. Interestingly, we found that the ACT group obtained a significantly higher AT following the training program compared to the PAS group. This could be because ACT allows a continuation of the training at a low intensity and may activate specific adaptive mechanisms that are not triggered during PAS.